Encyclopedia of Life Sciences 2007
DOI: 10.1002/9780470015902.a0020545
|View full text |Cite
|
Sign up to set email alerts
|

Histidine Triad ( HIT ) Superfamily

Abstract: Histidine triad (HIT) enzymes are an ancient superfamily of nucleotide hydrolases and transferases that catalyse mechanistically similar but biologically distinct reactions on nucleotide‐containing substrates in pathways important for cellular growth, apoptosis and deoxyribonucleic acid (DNA), ribonucleic acid (RNA) and carbohydrate metabolism. Four branches of HIT enzymes function as nucleotide hydrolases. These enzymes include homologues and paralogues of histidine triad nucleotide‐binding (Hint) protein, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…2A). An additional gene, mccH, is located 89 downstream of the mccB 1 gene and encodes a protein belonging to a histidine triad (HIT) 90 superfamily (12). We next attempted to reconstruct the production of each of the H. minutum compounds in a heterologous E. coli host.…”
Section: Hyalangium Minutum 83mentioning
confidence: 99%
See 1 more Smart Citation
“…2A). An additional gene, mccH, is located 89 downstream of the mccB 1 gene and encodes a protein belonging to a histidine triad (HIT) 90 superfamily (12). We next attempted to reconstruct the production of each of the H. minutum compounds in a heterologous E. coli host.…”
Section: Hyalangium Minutum 83mentioning
confidence: 99%
“…HinT Eco (19), and its human homologue, hHint1 (20, 21). The characteristic feature of the HIT 188 superfamily proteins is a conserved histidine triad motif, HxHxHxx, where H is a histidine, and x 189 are hydrophobic residues (12). The three essential catalytic histidines form a network of 190 hydrogen bonds with the substrate that promote proton transfer from protonated C-terminal 191 histidine of the triad (H103 in HinT Eco or H102 in HinT Hmi The loss of functional activity by MccH Hmi mutant K103H suggested that this residue, specific to 227…”
Section: Mutational Analysis Of Mcch Active Center 186mentioning
confidence: 99%